2017
DOI: 10.3389/fmed.2017.00191
|View full text |Cite
|
Sign up to set email alerts
|

Sterile Reverse Osmosis Water Combined with Friction Are Optimal for Channel and Lever Cavity Sample Collection of Flexible Duodenoscopes

Abstract: IntroductionSimulated-use buildup biofilm (BBF) model was used to assess various extraction fluids and friction methods to determine the optimal sample collection method for polytetrafluorethylene channels. In addition, simulated-use testing was performed for the channel and lever cavity of duodenoscopes.Materials and methodsBBF was formed in polytetrafluorethylene channels using Enterococcus faecalis, Escherichia coli, and Pseudomonas aeruginosa. Sterile reverse osmosis (RO) water, and phosphate-buffered sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 23 publications
1
17
0
1
Order By: Relevance
“…Our previous data showed that for 6639 CFU/mL of P. aeruginosa extracted from biofilm, there was only 1 RLU by the ATP test 9 . Furthermore, it took 7,424,795 CFU/mL extracted from biofilm to generate 1 μg/mL protein 9 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our previous data showed that for 6639 CFU/mL of P. aeruginosa extracted from biofilm, there was only 1 RLU by the ATP test 9 . Furthermore, it took 7,424,795 CFU/mL extracted from biofilm to generate 1 μg/mL protein 9 .…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, it took 7,424,795 CFU/mL extracted from biofilm to generate 1 μg/mL protein 9 . These data demonstrated that although rapid ATP and rapid protein testing are very useful for monitoring manual cleaning compliance, they are very insensitive and cannot act as a substitute for culture post-HLD 2 10 27 29 Unlike rapid ATP and protein testing that do not detect low levels of viable bacteria 9 23 25 26 27 29 the RN test was sensitive enough to reliably detect nine of nine suspension tests when there were ≥ 10 CFU of viable E. coli and P. aeruginosa in the 0.5-mL sample tested. This is an excellent limit of detection but it must be borne in mind that all the current guidelines for interpretation of endoscope cultures 8 18 19 indicate that even 1 CFU per channel of a Gram-negative bacteria is considered unacceptable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Das Ablösen von Biofilmen, z. B. bei Spülproben, hängt vor allem von den hierbei erzeugten Scherkräften ab [35]. Hierzu liegen bis jetzt für Endoskope keine Untersuchungen vor.…”
Section: Ablösen Von Biofilmbelägenunclassified
“…The use of a flush-only method for the channels is recognized as a potential limitation compared with use of a flush-brush-flush method. A study by Alfa et al, published in 2017, 63 stated that a flush-only method with the use of a tensioactive agent such as Tween 80 seemed less effective than a flush-brush-flush method and that the potential role of such agents in terms of sample extraction efficiency from endoscope channels needed to be further evaluated. Also, a study by Alfa et al published in 2017 64 stated that the use of a flush-brush-flush method improved recovery of bacteria in biofilms.…”
Section: Limitations Of the Studymentioning
confidence: 99%